Visible Spectrophotometric Methods for the Determination of Naratriptan Hydrochloride in Pure and Dosage Forms - Ramu, G.; Biksham Babu, A.; Murali Krishna, Ch.; Venkata Rao, S.; Rambabu, C. (Asian Journal of Chemistry, 2012)
Two simple, sensitive and reproducible visible spectrophotometric methods are developed for the determination of naratriptan hydrochloride in pure and its dosage forms. Method-A (brucine/ periodate) is based on the nucleophilic attack of bruciquinone on secondary nitrogen atom of substituted indole ring of the drug to give 1-monosubstituted bruciquinone derivative. In method- B (isatin/sulfuric acid) one mole of the lactam tautomeric form of the isatin condenses with secondary amine group in substituted indole ring of the drug in presence of concentrated sulphuric acid with the elimination of one mole of water. The absorption maximum and molar extinction coefficient are found to be 530 nm, 2.88 × 103 and 560 nm, 6.72 × 103 for method-A and method- B respectively. The developed methods are linear within the limits 12.5-70.0 μg/mL and 8.0- 48.0 μg/mL with correlation coefficient 0.9998 and 0.9991. These methods are precise, accurate and reproducible. The results of analysis are validated statistically and by recovery studies.